[Paper] Spatial Filter and Combination of Angle and Peristrophic Multiplexings to Achieve Recording Density of 1 Tbit/inch2 in Holographic Data Storage - Katano, Yutaro; Muroi, Tetsuhiko; Kinoshita, Nobuhiro; Ishii, Norihiko (ITE TRANSACTIONS ON MEDIA TECHNOLOGY AND APPLICATIONS, 2021)
We investigated the use of a spatial filter and a combination of multiplexing methods to obtain a data recording density of 1 Tbit/inch2. A small aperture diameter of the spatial filter can increase recording density, but the signal-to-noise ratio of the reproduced data decreases. We then investigated the minimum size of the aperture diameter under the condition where the data could be decoded. As a result, we found that the aperture diameter could be decreased to 1.2 times as large as the Nyquist width of a data page. To obtain a recording density of 1 Tbit/inch2, 800-data-page multiplexing was needed. We then investigated the recording conditions of angle and peristrophic multiplexings. When we recorded and reproduced data pages with 200 angle multiplexings and 4 peristrophic multiplexings, the bit error rates of the data were less than the permissive error rate, and a recording density of 1 Tbit/inch2 could be obtained.